Turkic - Johanson, Lars 1936- (Cambridge University Press, 2021)
Turkic is one of the world's major language families, comprising a high number of distinct languages and varieties that display remarkable similarities and notable differences. Written by a leading expert in the field, this landmark work provides an unrivalled overview of multiple features of Turkic, covering structural, functional, historical, sociolinguistic and literary aspects. It presents the history and cultures of the speakers, structures, and use of the whole set of languages within the family, including Turkish, Azeri, Turkmen, Tatar, Kazakh, Uzbek, and Uyghur, and gives a comprehensive overview of published works on Turkic languages, large and small. It also provides an innovative theoretical framework, employing a unified terminology and transcription, to give new insights into the Turkic linguistic type. Requiring no previous knowledge of the Turkic languages, it will be welcomed by both general readers, as well as academic researchers and students of linguistic typology, comparative linguistics, and Turkic studies
Title from publisher's bibliographic system (viewed on 24 Aug 2021)
Keywords: Turkic languages